Outcomes Book Debate and Consensus after the WPA Outcomes Statement - Harrington, Susanmarie; Rhodes, Keith; Fischer, Ruth; Malenczyk, Rita (University Press of Colorado, 2005)
The WPA Outcomes Statement is important because it represents a working consensus among composition scholars about what college students should learn and do in a composition program. But as a single-page document, the statement cannot convey the kind of reflective process that a writing program must undertake to address the learning outcomes described. The Outcomes Book relates the fuller process by exploring the matrix of concerns that surrounded the developing Statement itself, and by presenting the experience of many who have since employed it in their own settings.